Determinants of the Portuguese government bonds yields - Pinho, André Miguel dos Santos Castro (2018)
This paper makes an empirical analysis of the evolution of Portuguese government bonds yields in order to identify their main determinants for the period between 2000 and 2016 using quarterly data. An equation of the Portuguese government bonds yields is estimated considering three different maturities (one, five and ten years) and including eight independent variables (GDP, public debt, external debt, labour productivity, activity rate, inflation rate, stock market volatility and liquidity) to capture the global effects of credit risk, global risk aversion and the liquidity risk. Our main findings were that GDP growth rate, external debt, inflation rate and liquidity exert a positive effect on the ten year maturity sovereign bond yields while public debt, labour productivity, activity rate and the stock market volatility affect negatively the yields. Evidence supporting the contradictory sign of what the majority of the literature claims regarding public debt is also found. Overall, the results point out that there are no significant differences regarding the determinants of the government bonds yields for the different maturities. Finally, we conclude that the yields were harmful affected by liquidity, labour productivity but mostly by external debt. In turn, activity rate, GDP, public debt and mostly the inflation rate had a beneficial effect on the Portuguese government bonds yields.